Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s10067-016-3267-0
|View full text |Cite
|
Sign up to set email alerts
|

Fast 1.5 T chest MRI for the assessment of interstitial lung disease extent secondary to systemic sclerosis

Abstract: This study aims to evaluate the utility of magnetic resonance imaging (MRI) to assess interstitial lung disease (ILD) extent in patients with systemic sclerosis (SSc). Patients with SSc and varying degrees of ILD with a high-resolution computed tomography (HRCT), pulmonary function tests (PFTs), and a chest MRI containing an ultrafast SE sequence performed less than 1 year apart were included in the study. Wells global disease extent and Goh's staging algorithm were used to measure and categorize ILD both for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 25 publications
3
29
0
1
Order By: Relevance
“…This study demonstrated that HASTE MRI could detect patients with >0.5% ILD extent with a sensitivity of 93% and specificity of 100%. Furthermore, MRI showed the same diagnostic performance ( p=0.03) of thin-slices MDCT to detect ILD in systemic sclerosis patients [25]. RAJARAM et al [26] retrospectively analysed chest MRI of 224 patients, acquired using a two-dimensional balanced steady-state free-precession (bSSFP) sequence.…”
Section: Morphological Imagingmentioning
confidence: 98%
See 1 more Smart Citation
“…This study demonstrated that HASTE MRI could detect patients with >0.5% ILD extent with a sensitivity of 93% and specificity of 100%. Furthermore, MRI showed the same diagnostic performance ( p=0.03) of thin-slices MDCT to detect ILD in systemic sclerosis patients [25]. RAJARAM et al [26] retrospectively analysed chest MRI of 224 patients, acquired using a two-dimensional balanced steady-state free-precession (bSSFP) sequence.…”
Section: Morphological Imagingmentioning
confidence: 98%
“…However, HASTE imaging did not show a high diagnostic quality because of respiratory and cardiac motion artefacts [24]. PINAL-FERNANDEZ et al [25] evaluated the utility of HASTE to assess the extent of ILD involvement in patients with systemic sclerosis. HASTE showed a good diagnostic performance to detect ILD with an area under the curve of 96% (95% CI 89-100%).…”
Section: Morphological Imagingmentioning
confidence: 99%
“…Though still inferior to CT, current high-Tesla MRI machines can offer a radiation-free alternative for ILD detection. 23 A promising screening strategy for ILD can be the use of ultrasound (US). The number of B-lines ("comet" artifact) has shown correlation with CT scores 24 in SSc.…”
Section: Imagingmentioning
confidence: 99%
“…However, the frequent use of ionizing radiation is a matter of growing concern, especially in this population that already has an increased risk of tumors, as mentioned by Bastos et al (4) . Therefore, new imaging techniques, such as ultrasound of the thorax, the reduction in the number of HRCT slices, and the use of low-dose CT, have been proposed as options to resolve this problem (9) .…”
mentioning
confidence: 99%
“…However, the use of MRI is still limited to certain cases in which there is a need to minimize the use of ionizing radiation (9,10) . Allied to this problem, the upcoming addition of new antifibrotic drugs, such as pirfenidone (11) , to the therapeutic arsenal against SSc will further increase the challenges facing radiologists in the search for an ideal method to monitor patients with the disease.…”
mentioning
confidence: 99%